Nanovesicles system for rapid‐onset sublingual delivery containing sodium tanshinone IIA sulfonate: In vitro and in vivo evaluation. Issue 7 (23rd April 2013) - Zhu, Hongda; Hao, Jianjun; Chen, Huabing; Jiang, Shanshan; Liu, Mingxing; Sun, Honghao; Xu, Huibi; Zhang, Jiemei; Yang, Xiangliang
Abstract A novel formulation based on nanovesicles system for rapid‐onset sublingual delivery of hydrophilic drug (sodium tanshinone IIA sulfonate, STS) was investigated. The nanovesicles system was composed of 1.5% soybean lecithin, 6% propylene glycol, and penetration enhancers (1% sodium dodecyl sulfate and 0.03% hyaluronan acid). The STS‐loaded nanovesicles with an average diameter of 133 ± 9.04 nm and high entrapment efficiency of 85.65 ± 3.89% were characterized. The effects of permeation enhancers on the penetration of STS formulations were investigated using Franz diffusion cells in vitro, showing 86.1–235.8 times higher permeation rate than that of normal STS solution. The rapid symptom relief effect of the nanovesicles system on acute myocardial infarction rabbits was evaluated by in vivo study, ST‐segment deviation(S and T wave abnormality in electrocardiogram) was attenuated markedly and rapidly within 5 min, infarct size of heart was significantly reduced and the biochemical indicators were substantially decreased, compared with the control groups (p < 0.05). This study provided a promising tool for the future sublingual delivery of hydrophilic compounds with the noninvasive and rapid onset clinical effect. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2332–2340, 2013